Operator sequences of the aerobactin operon of plasmid ColV-K30 binding the ferric uptake regulation (fur) repressor. - de Lorenzo, V (1987)
The promoter region of the pColV-K30-encoded operon specifying biosynthesis and transport of the siderophore aerobactin was subjected to deletion analysis to determine the smallest DNA sequence affording iron regulation of a iucA'-'lacZ gene fusion. A 78-base-pair (bp) region containing the main (P1) promoter retained the character of inducibility under iron starvation. A 250-bp fragment carrying this sequence was examined for protection against DNase I by the Fur protein, the product of a gene (fur) required for negative control of several iron-regulated functions. The DNase I footprints, in the presence of various divalent heavy-metal ions added as corepressors, revealed two contiguous binding sites with different lengths and affinities for Fur. Increased concentrations of the protein appeared to elicit formation of repressor oligomers which bind to the upstream and downstream regions of the P1 promoter in a metal-dependent fashion, but with a presently undefined stoichiometry. The primary site for Fur binding spans 31 bp and contains two overlapping symmetry dyads which share the sequence 5'-TCATT-3'. It also contains extensive homology with a 19-bp consensus sequence for iron-regulated genes as deduced from comparison with the fhuA and fepA putative promoter sequences.